Social systems and community development: Cooperstown, New York, and its imitators. Issue 2 (14th March 2020) - Thomas, Alexander R.
ABSTRACT: This article explores a distinction between two types of community and economic development: System-Oriented Development (SOD) and Project-Oriented Development (POD). SOD is understood as the development that seeks to build on long-term trajectories in community evolution, and it is argued that such projects will have a higher chance of success. In contrast, POD is based on individual projects that are developed within a narrower range of concerns, and such projects are more likely to be successful when they accidentally tap into deeper systemic trajectories. Due to funding concerns and political considerations, POD is the more common of the two. The approaches are discussed within the context of a case study of the successful tourism economy in Cooperstown, New York, home to the Baseball Hall of Fame. Cooperstown is compared to the more limited success found in two other communities also home to sports shrines.